Pengaruh Event Marketing dan Brand Experience Terhadap Revisit Intention Pada Tasco Kota Tasikmalaya - Shita Nafilah Faza Faza; Rita Tri Yusnita; Titin Patimah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of event marketing and brand experience on revisit intention among Tasco consumers in Tasikmalaya City. This study uses a quantitative method with a causal approach and involves 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 25. The results show that event marketing and brand experience have a significant effect simultaneously on revisit intention. Event marketing has a positive e and significant effect in increasing consumer interest in returning to visit. In addition, brand experience also has a positive and significant effect with a greater contribution in shaping consumer desire to make repeat visits. These findings indicate that Tasco in Tasikmalaya City needs to optimize its event marketing strategy and strengthen its brand experience to increase consumer revisit intention sustainably.